A Method for Radioactive Labelling of Hebeloma cylindrosporum to Study Plant-fungus Interactions - Adeline Becquer; Margarita Torres-Aquino; Christine Le Guernevé; Laurie Amenc; Carlos Trives-Segura; Siobhan Staunton; Hervé Quiquampoix; Claude Plassard (Bio-Protocol, 2017)
In order to quantify P accumulation and P efflux in the ectomycorrhizal basidiomycete fungus Hebeloma cylindrosporum, we supplied 32P to mycelia previously grown in vitro in liquid medium. The culture had four main steps that are 1) growing the mycelium on complete medium with P, 2) transfer the mycelia into new culture solution with or without P, 3) adding a solution containing 32P and 4) rinsing the mycelia before incubation with or without plant. The main point is to rinse very carefully the mycelia after 32P supply in order to avoid overestimation of 32P efflux into the medium.